2021
DOI: 10.1111/andr.13126
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatments for obstructive sleep apnea decrease the risk of erectile dysfunction: A nationwide cohort study

Abstract: Background: It has been reported that the risk of erectile dysfunction (ED) is significantly higher in patients with obstructive sleep apnea (OSA), compared with patients without OSA. However, there is limited evidence on whether surgical treatments in patients with OSA could decrease ED risk. Objectives:To assess the impact of surgical treatments for OSA on the risk of ED by analysis of claims data from the Taiwan National Health Insurance Research Database between 1997 and 2012. Material and methods:We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It has been proved that CPAP therapy significantly improves erectile function of OSA patients, and a combined treatment with sildenafil provides a cumulative effect [36]. In addition, a large and long-term cohort study which included 11,116 OSA patients has shown that surgical treatments for OSA could reduce the risk for developing ED by 21% [37]. In P r e p r i n t 11 our research, we have not identified genetic evidence of a causal relationship between OSA and ED.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that CPAP therapy significantly improves erectile function of OSA patients, and a combined treatment with sildenafil provides a cumulative effect [36]. In addition, a large and long-term cohort study which included 11,116 OSA patients has shown that surgical treatments for OSA could reduce the risk for developing ED by 21% [37]. In P r e p r i n t 11 our research, we have not identified genetic evidence of a causal relationship between OSA and ED.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, surgical treatment may reduce the risk of primary brain cancers in subjects with OSA [ 3 ]. Recently, we found that surgical treatments could reduce the risk of erectile dysfunction in OSA patients by a large-scale cohort study [ 5 ]. This study showed that surgical treatment for OSA in CKD patients could decrease ESRD risk, but increase mortality risk, especially for non-cardiovascular mortality and within 3 months after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded 19,510 CKD patients who were aged < 18 years, had missing data, had a diagnosis of ESRD or OSA before the CKD inception date, and expired or dropped out before the CKD inception date; we obtained 357,299 CKD patients without OSA. We further identified 32,220 incident OSA patients after the CKD inception date and divided them into two groups according to exposure to surgical treatment for OSA, which was defined as ever admission due to OSA or the presence of ICD-9/10 surgical procedure codes for OSA [ 5 ]. CKD patients who ever received surgical treatments for OSA between 2001(1 year after the start of the LGTD2005 inclusion period) and 2015 (1 year before the end of the LGTD2005 inclusion period) were designated as the treated cohort ( n = 1171).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation